In silico Investigation of Coumarin-based Compounds Targeting Keap1-Nrf2 Pathway Involved in the Development of Alzheimer’s Disease - Gote, Sharmila; Dubey, Sonal; Nargund, Shachindra; Thapa, Shankar (Letters in Drug Design & Discovery, 2024)
BackgroundThe Nrf2-Keap1 pathway holds great significance in antioxidant defense mechanisms. This pathway has emerged as a pivotal clinical target for the development of highly potent therapeutic agents for neurodegenerative diseases. The Keap1-Nrf2 inhibitors covalently bind to the Keap1 protein, leading to modifications in cysteine residues. This computational study focused on the investigation of coumarin derivatives through in silico methods.ObjectiveThe aim of this study was to conduct an in silico exploration of coumarin derivatives as potential Keap1 inhibitors in the context of Alzheimer's disease.MethodsCoumarin derivatives were obtained from the ZINC 15 database in the sdf (simple dimension file) format. The docking process utilized the crystal structure of the Keap1 protein (PDB ID: 4XMB), which was sourced from the RCSB Protein Data Bank (https://www.rcsb.org/). Molecular docking was conducted using the AutoDock Vina1.5.7 software. Following this, the top ten coumarin derivatives with the highest binding energy underwent an ADME study, SAR study, toxicity study, and medicinal chemistry score study. In the in silico study, resveratrol was employed as the standard drug.ResultsWe sourced ligand molecules from the ZINC 15 database in pdf format, while the Keap1 protein, identified by its PDB ID: 4XMB, was obtained from the RCSB website (https://www.rcsb.org/) in pdb format. We used resveratrol as the standard drug for the molecular docking analysis. The in silico molecular docking procedures were conducted using Autodock Vina 1.5.7 software.ConclusionAmong the 75 coumarin derivatives assessed, 9 exhibited the most favourable binding energies towards Keap1. The top 9 derivatives of coumarin were further scrutinized in terms of their pharmacokinetic profiling and evaluation of bioactivity. Both compounds S1 and S2 exhibited noteworthy docking scores of -7.44 and -7.52 Kcal/mol, respectively. Our investigation revealed that all nine derivatives of coumarin exhibited properties characteristic of drug-like compounds. The investigation conducted suggested the potential development of coumarin derivatives as effective Keap1-Nrf2 inhibitors. Further validation of the computational findings requires both in vivo and in vitro studies.
Keywords: Keap1